2x+3-3x=7

Simple and best practice solution for 2x+3-3x=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+3-3x=7 equation:


Simplifying
2x + 3 + -3x = 7

Reorder the terms:
3 + 2x + -3x = 7

Combine like terms: 2x + -3x = -1x
3 + -1x = 7

Solving
3 + -1x = 7

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + -1x = 7 + -3

Combine like terms: 3 + -3 = 0
0 + -1x = 7 + -3
-1x = 7 + -3

Combine like terms: 7 + -3 = 4
-1x = 4

Divide each side by '-1'.
x = -4

Simplifying
x = -4

See similar equations:

| (-4+-1x^2)=0 | | (2+5)*(12+18)*40+3238+500= | | .80x+2.30=30 | | 9x-5=1+6x | | 6m=-6+144 | | [21+(-21)]+[21+(-25)]= | | 10m-29=71whatsm | | 3w+8x-13y+6w+7x+8y= | | 10y=2x-13 | | ln(e^4*x)+8=0 | | 14x+40=360 | | -8+10-(-7)-20+19= | | X^2+x-1=5x | | ln(e^4x)+8=0 | | 2X+3Y+8+2X+4+1Y=360 | | t=25-0.25n | | 0.20+1x=0.25 | | -9(10)= | | 6f+2f+f=180 | | 4(x-10)=-6(2-2x)-6 | | 0=3n^2-10n+4 | | 4x-71=94-7x | | x-(-2)=(-7) | | 7y+5x=14 | | 3a-(5a-4)=-4 | | -9x-49=39-5x | | 6x+20y=30 | | 20x+13g-13x= | | -6x-35=-8x+11 | | x-2=(-7) | | 5x-40=11+2x | | -122+6x=-5x+53 |

Equations solver categories